A spoke type permanent magnet motor - Raja Nor Firdaus Kashfi, Raja Othman; Kasrul, Abdul Karim; Mohd Luqman, Mohd Jamil; Md Nazri, Othman (2015)
The present invention discloses a spoke type permanent magnet motor comprises a stator assembly having at least one back iron on which coils are wound, and a rotor assembly rotatably disposed within the stator assembly; wherein the rotor assembly comprises a shaft radially surrounded by means for accommodating at least one magnet, and a support unit configured to hold the magnet accommodating means onto the shaft 6 and to separate the two at a predetermined distance so that at least one hollow section is formed between the shaft and the magnet accommodating means.